PENGARUH KOMUNIKASI INTERPERSONAL DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN CV.STELLA CATERING - Rianof, Firnanda; Malik, Abdul (JURNAL MUTIARA MANAJEMEN, 2022)
This study aims to determine and analyze the effect of interpersonal communication and work motivation on employee performance CV. Stella Catering. The sampling technique used a saturated sample of 40 respondents. The data collection method used a questionnaire/questionnaire. The results of multiple linear regression analysis obtained the equation Y = 6.448 + 0.353X1 + 0.527X2. In the partial test (t test) the interpersonal communication variable has a positive and significant effect on employee performance with a t-count value of 2.395 > t-table 2.026 and a significant value of 0.022 <0.05 and the work motivation variable has a positive and significant effect on employee performance with a t-value count is 3.495 > t table 2.026 and the significant value is 0.001 < 0.05. Simulative significant test results (F test) interpersonal communication and work motivation variables have a positive and significant effect on employee performance with a calculated F value of 70.552 > F table 3.25 and a significant value of 0.000 <0.05. The results of the coefficient of determination test (R2) obtained an R Square value of 0.792, meaning that the employee performance variable can be explained by 79.2% by interpersonal communication and work motivation variables, while the remaining 20.8% is explained by other variables not included in this study.